The Influence Exerted by a Restricted Phospholipid Microenvironment on the Expression of Tissue Factor Activity at the Cell Plasma Membrane Surface - Kunzelmann-Marche, Corinne; Satta, Nathalie; Toti, Florence; Zhang, Youming; Nawroth, Peter P.; Morrissey, James H.; Freyssinet, Jean-Marie (Thrombosis and Haemostasis, 2000)
Phosphatidylserine (PhtdSer) is an anionic aminophospholipid necessary for the development of optimal tissue factor (TF) activity at the cell surface. This study investigates the implication of a restricted lipid environment with respect to PhtdSer availability on TF expression and activity. K562 cells, showing a reduced ability to externalize PhtdSer, were transfected with human TF cDNA. PhtdSer exposure and TF activity were examined in transfected cells and compared to monocytic THP-1 cells expressing constitutive and inducible TF or megakaryocytic HEL cells showing a high PhtdSer externalization potency. TF expression was evidenced by flow cytometry and its activity measured using functional assays. PhtdSer exposure was monitored by enzymatic prothrombinase assay. One clone (DC9) expressed a stable amount of TF antigen without global modification of its membrane status. Despite a noticeable TF expression level, clone DC9 presented only a weak TF activity even after ionophore stimulation. The apparent Km, relative to factor X (FX) activation by TF-factor VIIa (FVIIa) complex, was 335 nM versus 70 nM for THP-1 cells. The velocity of the reaction was found 3-fold slower in DC9 than THP-1 cells. Ionophore treatment resulting in slightly enhanced amounts of available PhtdSer abolished this difference. The DC9 clone appears suitable for further investigations on the biology of TF expressed at the surface of cells where the contribution of PhtdSer is significantly attenuated. Such cells should enable further assessment of the role of TF as a receptor coupled to intracellular signaling pathways and its fate during apoptotic cell death.Abbreviations: TF: tissue factor, FX: factor X, FVII(a): factor VII(a), PhtdSer: phosphatidylserine, PhtdCho: phosphatidylcholine, PhtdEth: phosphatidylethanolamine, BSA: bovine serum albumin, dcTF: des-cyto tissue factor (TF1-244: membrane-anchored TF lacking the cytoplasmic tail)
Keywords: Tissue factor; phosphatidylserine; K562 cells; procoagulant activity; microparticle release